2014
DOI: 10.1080/15627020.2014.11407642
|View full text |Cite
|
Sign up to set email alerts
|

Home range, habitat selection and activity patterns of an arid-zone population of Temminck’s ground pangolins, Smutsia temminckii

Abstract: All previous behavioural studies of Temminck's ground pangolins (Smutsia temminckii) have focused on populations in mesic regions. We examined home range size, activity periods, habitat selectivity and refuge site selection of 13 individuals over three years in the Kalahari Desert of South Africa, near the western edge of the species' range. Kernel home ranges of adults averaged 6.5 ± 5.9 km², while juveniles had average home ranges of 6.1 ± 4.0 km². Reliable prediction of 95% of the Kernel home range required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 10 publications
4
16
0
Order By: Relevance
“…K. Abernethy, personal communication, July 2017) indicate that giant ground pangolins may be active in the day as well. This is not without precedent as white-bellied pangolins ( Phataginus tricuspis [Rafinesque, 1821]), black-bellied pangolins ( P. tetradactyla [Linnaeus, 1766]) and Temminck’s ground pangolins are known to be active in the day (Pietersen et al., 2014). The presence of multiple burrow entrances around the active pangolin burrow prohibits any confident conclusions about the activity patterns of giant ground pangolins, such as how long they remain in burrows, when they enter and exit, on average, and whether they use multiple burrows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…K. Abernethy, personal communication, July 2017) indicate that giant ground pangolins may be active in the day as well. This is not without precedent as white-bellied pangolins ( Phataginus tricuspis [Rafinesque, 1821]), black-bellied pangolins ( P. tetradactyla [Linnaeus, 1766]) and Temminck’s ground pangolins are known to be active in the day (Pietersen et al., 2014). The presence of multiple burrow entrances around the active pangolin burrow prohibits any confident conclusions about the activity patterns of giant ground pangolins, such as how long they remain in burrows, when they enter and exit, on average, and whether they use multiple burrows.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of the habitat requirements and activity patterns, as well as natural history observations, will need to be augmented with remotely sensed data, such as telemetry and camera-trap studies. Giant ground pangolins have never been tagged or tracked to date, though other pangolin species have (Nebo & Rankin, 2011; Pagés, 1975; Pietersen, McKechnie, & Jansen, 2014; Sun, Lin, Lai, & Pei, 2015). Temminck’s ground pangolin ( Smutsia temminckii [Smuts, 1832]) habitat use has been studied by following animals that have radio transmitters attached and remotely sensed information collected through GPS receivers (Pietersen et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pangolins ranged in weight from 3.4 to 15.1 kg and in length (nose to tail tip) from 53 to 114 cm. It has been suggested that Temminck's pangolins weighing <6 kg are juvenile while those weighing >6 kg are adult (2). Five animals in the reference sample population weighed <6 kg.…”
Section: Study Population and Sample Analysismentioning
confidence: 99%
“…Pangolins (Order: Pholidota; Family: Manidae) are myrmecophagous (eat only ants and termites), scaled, toothless mammals. Pangolins are shy, nocturnal animals, rarely encountered in the wild and difficult to keep in captivity due to their dietary requirements, lack of provision of a suitable habitat and apparent susceptibility to infectious diseases (1,2). They are the most trafficked non-human mammal in the world, and have recently received even more notoriety as potential intermediate hosts of SARS-CoV-2 (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%